Microsoft Sees Software 'Agent' as Way to Avoid Distractions - Horvitz, Eric (New York Times, On the Web (Technology), 2000)
REDMOND, Wash. – Attention, please. Hoping to shed its longstanding industry reputation as a mere imitator, not an innovator, Microsoft is spending heavily on research in a wide range of software technologies that include hand-held computing and voice recognition. But the most intriguing project may be taking place in the cramped office of Eric Horvitz, a devotee of an obscure, 17-century statistical technique that plays a key role in his current work.